Transformations of tradition - Quadri, Junaid. (New York, NY)
xiii, 243 sayfa
Keywords: “Transformations of Tradition probes how the encounter with colonial modernity conditioned Islamic jurists' conceptualizations of the shari'a. Departing from the tendency to focus on reformist-minded thinkers and politically charged issues, Junaid Quadri directs his attention towards the overlooked jurisprudential writings of Muhammad Bakhit al-Muti-i (1854-1935), Mufti of Egypt and a frequent critic of the famed reformists Muhammad 'Abduh and Rashid Rida. There, he locates a remarkable series of foundational intellectual shifts. Offering a fresh perspective on a pivotal period in the history of Islamic thought, Quadri tracks how Bakhit reworks the relationship of the shari'a to categories of understanding as fundamental as history and authority, science and technology, and religion and the secular, thereby upending the very ground upon which Islamic law had until then functioned. Through close readings of complex legal texts and mining of oft-neglected archives, this carefully researched study situates its argument in both the contested scholarly world of a quickly-changing Cairo, and the transregional school of Hanafi law as represented by jurists writing in Kazan, Lucknow, and Baghdad. Examining Islamic jurisprudential discourse in the colonial moment, Transformations of Tradition uncovers a shari'a that is neither a medieval holdover nor merely a pragmatic concession to the demands of a new world, but rather deeply entangled with the epistemological commitments of colonial modernity“--